The Management Library of Senior High School Number 2 OKU - Andesta , Tamalia; Fitria, Happy; Fitria, Yessi (Jurnal Pendidikan Tambusai, 2021)
This study aims to identify and describe (1) the management of human resources in the SMA Negeri 2 OKU library, (2) the management of library collections at SMA Negeri 2 OKU and (3) maintenance of library collections at SMA Negeri 2 OKU. The method used is a qualitative method. Data collection techniques using observation, interviews and documentation. The results of the study can be concluded that the management of human resources of the OKU Public Senior High School 2 library starts from the recruitment of library staff, library staff at SMA Negeri 2 OKU, the management of the library collections of the OKU Public High School 2 starts with conducting internal library coordination meetings, during the meeting. will discuss the planning of library material processing including inventory activities, classifying, cataloging, making library completeness, compiling catalog cards, compiling books and magazine processing. And the maintenance of the library collection of the OKU 2 Public Senior High School library is adjusted to the level of damage, namely for the level of small, medium to severe damage or those that cannot be used anymore.